Evaluation of neck dissection with frozen section biopsy – Management of levels IV and V - Frohwitter, Gesche; Röckl, Jonas; Rau, Andrea; Wolff, Klaus Dietrich; Kesting, Marco Rainer; Koerdt, Steffen (Journal of Cranio-Maxillofacial Surgery, 2019)
Introduction: Neck dissection is an essential component of oral cancer therapy. Based on a standardised approach to cervical lymph node management, we seek to define the relevance of neck dissection extension in cN + cases. Material and methods: A retrospective analysis from January 2009 to February 2017 identified 84 patients with oral squamous cell carcinoma with a cN + neck or histologically proven lymph node involvement in intraoperative frozen sectioning and who received modified radical neck dissection according to the presented neck dissection algorithm. Results: Overall 11 patients showed lymph node metastasis level IV or V, whereas 19 developed disease recurrence, of which 5 cases were neck recurrences. A total of 30 patients died within the time of observance (overall survival of n = 54). None of those patients with pN + status in levels IV and V reached a 5-year survival. Discussion: With a look to the possibility of a 5-year survival in patients with a N+ status in level IV and V, the justification for a radical approach to the neck appears questionable. However, modified radical neck dissection appears to be a suitable for a high-risk oral cancer subgroup. A randomised controlled trial is needed to define guidelines for the neck dissection extent in c/pN + cases.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Disease-free survival; Level IV and V; Modified radical neck dissection; Oral cancer; Overall survival; Supraomohyoid neck dissection